Analysis of a vacuum-based photovoltaic thermal collector - Ali Radwan; Takao Katsura; Saim Memon; Essam M. Abo-Zahhad; Ahmed A. Serageldin; Katsunori Nagano (Energy Reports, 2020)
In this study, a new design of photovoltaic thermal (PV/T) collector is proposed. This design uses a vacuum layer above the silicon wafer and not exists in the traditional PV/T collector. This layer is used to decrease the heat loss from the top surface of the PV/T collector. The analysis is conducted using a 3D thermal modeling. The new collector design with the vacuum layer achieved a 26.6% increase in the thermal power while keeping the electrical the same at Reynolds number of 50 and solar radiation of 1000 W/m2. In addition, the degradation of the vacuum pressure slightly influence the thermal performance while increasing the vacuum pressure from 0.01 Pa to 10 Pa. While further increase in the vacuum pressure from 10 Pa to 1.013×105 Pa substantially decreases the gained thermal power with insignificant increase in the electrical power.